Male infertility problems of patients with strict sperm morphology between 5–14% may be missed with the current WHO guidelines. (2nd November 2018) - Jensen, Christian Fuglesang S.; Khan, Omar; Nagras, Zainab G.; Sønksen, Jens; Fode, Mikkel; Østergren, Peter B.; Shah, Tariq; Ohl, Dana A.; ,
Abstract: Objective: In 2010 W.H.O. changed the lower reference limit for strict sperm morphology from 15 to 4%. The change was based on 5 th percentile cut points from a meta-analysis on a published series of fertile men. This study investigates if patients referred for evaluation with sperm morphologies between 5–14% have identifiable etiologies of male infertility. Materials and methods: I.R.B. approval was obtained to review records for patients referred to the University of Michigan Center of Reproductive Medicine between May 2012–May 2014 whom had a sperm morphology of 5–14%. Semen analysis, hormone levels, and information related to an infertility diagnosis, were recorded into a de-identified database. Patients were placed into the categories 'Varicocele', 'Hypogonadism', 'Intercourse problems', 'Anti-sperm antibodies (A.S.A.)', 'Other' or 'No diagnosis'. Results: A total of 253 patients were included in the study. Of these, 96/253 (38%) had a clinical varicocele; 44/253 (17%) hypogonadism; 4/253 (2%) intercourse problems; 11/253 (4%) evidence of sperm antibodies; and 15/253 (6%) had various other problems deemed potentially contributing causes of infertility. In all, nearly 67% of the subjects were identified to have a potential contributing etiology of male infertility. Similar results were found for the men with isolated low morphology ( n  = 194). Conclusions: This study demonstrates that 67% of men in infertile couples, who have strict sperm morphology between 5 and 14%, are found to have a potential contributing male factor infertility diagnosis. This raises the possibility that the new lower reference value for sperm morphology may result in missed opportunities for proper infertility assessment.